Effects of live weight adjusted feeding strategy on plasma indicators of energy balance in Holstein cows managed for extended lactation. (16th November 2015) - Gaillard, C.; Vestergaard, M.; Weisbjerg, M. R.; Sehested, J.
Abstract : In early lactation, most of the dairy cows are in negative energy balance; the extent and duration depend in part on the feeding strategy. Previous studies showed an increased lactation milk yield by use of a live weight (LW) adjusted feeding strategy with a high energy diet before and a reduced energy diet after LW nadir compared with a standard diet throughout lactation. The objective of the present study was to examine how such an individualized feeding strategy affects plasma indicators of energy status. It was hypothesized that an energy-enriched diet until LW nadir will reduce the severity of the negative energy balance, and that the reduction in diet energy concentration from LW nadir will extend the negative energy balance period further. Sixty-two Holstein cows (30% first parity) were managed for 16 months extended lactation and randomly allocated to one of two feeding strategies at calving. Two partially mixed rations were used, one with a high energy density (HD) and a 50 : 50 forage : concentrate ratio, and one with a lower energy density (LD, control diet) and a 60 : 40 forage : concentrate ratio. Half of the cows were offered the HD diet until they reached at least 42 days in milk and a LW gain⩾0 kg/day based on a 5-days LW average, and were then shifted to the LD diet (strategy HD-LD). The other half of the cows were offered the LD diet throughout lactation (control strategy LD-LD). Weekly blood samples were drawn for analysis of plasma metabolites and hormones. Before the shift in diet, the HD-LD cows had higher glucose and lower beta-hydroxybutyrate and non-esterified fatty acids (NEFA) concentrations than the LD-LD cows. After the shift until 36 weeks after calving, plasma NEFA was higher in HD-LD than LD-LD cows. Insulin and insulin-like growth factor-1 were not affected by the feeding strategy. To conclude, in early lactation, the energy-enriched diet reduced the negative energy balance. Plasma NEFA was higher in HD-LD than LD-LD cows from diet shift until 36 weeks after calving, indicating a carry-over effect of the early lactation HD diet to late lactation metabolism.